Beautiful Bottom, Beautiful Shame : Where "Black" Meets "Queer" - Stockton, Kathryn Bond, 1958- (Book collections on Project MUSE., 2006)
The author explores dramatic switchpoints between the terms 'black' and 'queer', with reference to matters such as the stigmatized 'skin' of some queers' clothes and the visual power of interracial homosexual rape.